Enhancement of Students’ Artistic Talents through Formation of Projective-Research Knowledge, Skills and Abilities - Абдулахадова, Шохида (АКТУАЛЬНОЕ В ФИЛОЛОГИИ, 2021)
in this article, the advantages of fulfilling the projective-researching performance while arranging creational upbringing in a comprehensive-secondary institution.